COVID-19 infection fatality rate: a new approach - S., Seshadri M.; R., Ranganathan C. (International Journal Of Community Medicine And Public Health, 2020)
Infection fatality rate (IFR) in COVID 19 is a useful parameter for health-care planning during the current COVID-19 pandemic. The sensitivity of the reverse transcription polymerase chain reaction (RT-PCR) test, the rate of mortality reporting (MRR) in a country and the number of RT-PCR tests done per million population are the factors that influence the true infection fatality rate. In this article we present a ready reckoner for estimating the infection fatality rate for COVID-19, for a given RT PCR test sensitivity and mortality reporting rate for use in middle and low-income countries with resource constraints. We further demonstrate the inverse relationship between infection fatality rate and the number of tests done.